Pengaruh Fotografi Makro sebagai Media Pembelajaran untuk Menarik Minat Peserta Didik dalam Kegiatan Belajar Mengajar - Engalydva Ralasepty Syopyan; Maya Purnama Sari (Universitas PGRI Semarang, 2021)
The role of learning media for educators or teachers can be a supporting role in teaching and learning activities. Macro photography or photography with the process of magnification of a small subject can be used as one of the learning media used in teaching and learning activities. The research uses qualitative methods where this method is descriptive, uses analysis that refers to the data obtained, and utilizes existing theories for supporting materials, as well as producing a theory. The purpose of this research is to know the influence of macro photography when used as a learning medium in teaching and learning activities. The results of the study by spreading questionnaires online stated that 96% of students feel attracted to images taken using macro photography techniques Students' curiosity to learn new things is further increased When presented images with macro photography techniques because the images presented look more detailed, and visible beauty that sometimes can not be seen with the naked eye from afar.